Comparative Adsorption Studies of Methyl Orange Using Different Varieties of Melon Seeds as Adsorbents - Zahra, Asmat; Imran, Muhammad; Kanwal, Farah (Asian Journal of Chemistry, 2012)
In the present study seeds of melon, watermelon and muskmelon were used for the removal of methyl orange from aqueous media. It was observed that the efficiency of the three adsorbents was dependant on various parameters such as concentration of analyte, concentration of adsorbent, particle size, pH, temperature, time and stirring. It was found that maximum adsorption occurred at 80 mesh with value of 40 % for melon seed, 33.3 % for muskmelon seed and 2.70 % for watermelon seed. It can be concluded from this study that low adsorbent dose, low dye concentration, low contact time, low pH, low temperature and low stirring are the most favourable conditions for the adsorption of methyl orange dye on all three adsorbents. The comparative behaviour of these three adsorbents further indicates that muskmelon seed is a better adsorbent than watermelon seed and melon seed.